First insight into host ant use of the scarce large blue Phengaris teleius (Lepidoptera: Lycaenidae) in Ljubljansko barje (Central Slovenia) - Barbara Zakšek; Gregor Bračko; Nika Kogovšek; Marijan Govedič; Valerija Zakšek (Natura Sloveniae)
First data on the host ant use of the scarce large blue Phengaris teleius in Ljubljansko barje are presented herewith. A survey was carried out in 2021 in the vicinity of the Bevke village. Altogether, 59 Myrmica ant nests were surveyed for the presence of scarce large blue caterpillars, 58 of M. scabrinodis and one of M. rubra. We found four caterpillars of the scarce large blue in three M. scabrinodis ant nests. Our results indicate that M. scabrinodis is probably the main host of Phengaris teleius in Ljubljansko barje, the same as in other regions of Europe.